2010
DOI: 10.1128/jb.01623-09
|View full text |Cite
|
Sign up to set email alerts
|

RecA4142 Causes SOS Constitutive Expression by Loading onto Reversed Replication Forks inEscherichia coliK-12

Abstract: Escherichia coli initiates the SOS response when single-stranded DNA (ssDNA) produced by DNA damage is bound by RecA and forms a RecA-DNA filament. recA SOS constitutive [recA(Con)] mutants induce the SOS response in the absence of DNA damage. It has been proposed that recA(Con) mutants bind to ssDNA at replication forks, although the specific mechanism is unknown. Previously, it had been shown that recA4142(F217Y), a novel recA(Con) mutant, was dependent on RecBCD for its high SOS constitutive [SOS(Con)] expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 47 publications
(42 reference statements)
1
9
0
Order By: Relevance
“…It was found that SOS expression in recA4142 (F217Y) mutants was dependent on its initial level of transcription, recBCD, ruvAB, recJ, and xonA. The data are consistent with the model that the loading of RecA4142 occurs at reversed replication forks (28). Furthermore, it was found that recX and xthA repressed the level of SOS constitutive expression in the recA4142 mutant (29).…”
supporting
confidence: 77%
See 2 more Smart Citations
“…It was found that SOS expression in recA4142 (F217Y) mutants was dependent on its initial level of transcription, recBCD, ruvAB, recJ, and xonA. The data are consistent with the model that the loading of RecA4142 occurs at reversed replication forks (28). Furthermore, it was found that recX and xthA repressed the level of SOS constitutive expression in the recA4142 mutant (29).…”
supporting
confidence: 77%
“…Constitutive SOS expression in the recA4142 (F217Y) mutant is dependent upon ruvAB (28,29). Since radA is partially redundant with ruvAB for UV survival and recombination (1), it is possible that radA may also be required for SOS expression in a recA4142 mutant and that the deletion of radA should lower SOS expression.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several of these types of mutants have been described (reviewed in [36]). It has been shown for two of these mutants, recA4142 (F217Y) and recA730 (E38K), that while they both cause SOS constitutive (SOS C ) expression, they do so through different mechanisms [3739]. SOS C expression in recA4142 mutants depends on several genes: recBCD, ruvAB, recJ and sbcB [37].…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown for two of these mutants, recA4142 (F217Y) and recA730 (E38K), that while they both cause SOS constitutive (SOS C ) expression, they do so through different mechanisms [3739]. SOS C expression in recA4142 mutants depends on several genes: recBCD, ruvAB, recJ and sbcB [37]. It was proposed that RecBCD loads RecA4142 onto the ends of a replication fork that has been reversed by RuvAB and tailored by RecJ and SbcB.…”
Section: Introductionmentioning
confidence: 99%